The Flying Wing Car - Bassim, Hussein Medhat; El Shamy, Iman Abd El Salam (International Journal of Advanced Research in Engineering; Vol 1 No 3 (2015): International Journal of Advanced Research in Engineering, 2015)
The flying wing Car uses all outside surfaces to gain lift and maximize aerodynamic lift .The body and construction is based on ultralight and light-aircraft technologies.The use of compressed air to shape the outside structures to change the lift and drag according to the needs of flight..